2012
DOI: 10.1002/cbdv.201100345
|View full text |Cite
|
Sign up to set email alerts
|

Novel Zierane‐ and Guaiane‐Type Sesquiterpenes from the Root of Melicope denhamii

Abstract: Two novel zierane-type sesquiterpenes, named melicodenones A and B (1 and 2, resp.), and three new guaiane-type sesquiterpenes, named melicodenones C-E (3-5), were isolated from the root of Melicope denhamii (Seem.) T. G. Hartley together with zierone (6). Their structures were established by extensive NMR-spectroscopic analyses. Compounds 1-6 were tested for cytotoxicity using human colon cancer DLD-1 cells, and melicodenone A (1) was found to exhibit moderate activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…The NOESY correlations of H-10/H 3 -13 suggested the cofacial arrangement of H 3 -15 and 7-OH. In addition, the cis -disposition of H-1 and H-10 was deduced from chemical shift of H-10 ( δ H 2.08) and H 3 -15 ( δ H 0.65) in 1 H NMR spectrum recorded in CDCl 3 [5,25]. The overall pattern of experimental ECD spectrum of compound 3 matched well with the calculated ECD curve for (1 S , 7 R , 10 S ) isomer (Figure 4), demonstrating the (1 S , 7 R , 10 S ) absolute configuration for compound 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The NOESY correlations of H-10/H 3 -13 suggested the cofacial arrangement of H 3 -15 and 7-OH. In addition, the cis -disposition of H-1 and H-10 was deduced from chemical shift of H-10 ( δ H 2.08) and H 3 -15 ( δ H 0.65) in 1 H NMR spectrum recorded in CDCl 3 [5,25]. The overall pattern of experimental ECD spectrum of compound 3 matched well with the calculated ECD curve for (1 S , 7 R , 10 S ) isomer (Figure 4), demonstrating the (1 S , 7 R , 10 S ) absolute configuration for compound 3 .…”
Section: Resultsmentioning
confidence: 99%
“…181 Melicodenones C-E 557-559 are another three compounds of this type, which have been discovered in an extract of the roots of Melicope denhamii. 396 A chemical study of cell cultures of Stellera chamaejasme 397 afforded the guaiane sesquiterpene 560-562. The structures of rupestines F-M have been determined as 563-570.…”
Section: Germacranementioning
confidence: 99%
“…462 Melicodenone A 693 and melicodenone B 694 are two new zierane derivatives, which have been isolated from the roots of Melicope denhamii. 396…”
Section: Germacranementioning
confidence: 99%
“…The utilization of this plant is undoubtedly associated with secondary metabolites. Based on literature studies, secondary metabolites found in Melicope plants include alkaloids, coumarins, flavonoids, benzopirans, and terpenoids [2][3][4][5][6][7]. Recently, the Plasmodium parasites, showing resistance to malaria drugs such as chloroquine and artemisinin [8].…”
Section: ■ Introductionmentioning
confidence: 99%